Toxicity mechanism analysis of cGAS-STING-TBK1 signaling pathway small molecule modulator based on network toxicology and molecular docking strategy: quinacrine acetate as an example - Jinchao Zhu; Qingyuan Lin; Honglin Zhu; Siqi Xie; Shengdong Nie (Frontiers in Chemistry)
ObjectiveThis study aims to investigate the toxicity characteristics and mechanisms of quinacrine acetate, a small molecule modulator of the cGAS-STING-TBK1 signaling pathway, and to establish and validate the application value of network toxicology analysis strategy.MethodsProTox and ADMETlab platforms were used to evaluate the toxic effects of quinacrine acetate on human tissues and organs. Potential targets associated with quinacrine acetate toxicity were identified through ChEMBL, STITCH, GeneCards, OMIM, and TD databases. GO and KEGG analyses were employed to elucidate related functions and molecular mechanisms. STRING and Cytoscape software were utilized to identify key hub genes, while molecular docking validation was performed using the CB-Dock2 database. Based on toxicity analysis results, COPD was selected as a disease model, and GEO database was used to analyze the expression characteristics, immune correlation, and drug target value of hub genes in COPD.ResultsProTox and ADMETlab analyses revealed that quinacrine acetate exhibited significant toxicity to the respiratory system (toxicity level 4, risk coefficient 0.959). Through integrated multi-database analysis, 14 potential targets related to quinacrine acetate-induced respiratory system toxicity were identified. GO and KEGG pathway analyses indicated that quinacrine acetate-induced respiratory toxicity was primarily mediated through metabolic pathways. Network analysis via STRING and Cytoscape identified AKT1, PLA2G4A, and ALOX5 as three core targets. Molecular docking results confirmed strong binding affinity between quinacrine acetate and these core targets. In COPD patients, PLA2G4A and ALOX5 showed significantly upregulated expression, with hub gene ROC curve AUC value reaching 0.829, demonstrating good diagnostic value. Further immune correlation analysis revealed that ALOX5 and PLA2G4A were closely associated with various immune cell expressions and served as targets for multiple drugs including histamine, melittin, and formic acid.ConclusionThis study demonstrates that quinacrine acetate may influence the progression and risk of respiratory system diseases by regulating metabolic pathways. The findings provide not only a theoretical foundation for understanding the molecular mechanisms of quinacrine acetate-induced respiratory toxicity but also new perspectives and methodological references for evaluating the toxic effects of small molecule compounds in respiratory diseases. Therefore, we demonstrates the practical application value of network toxicology as an efficient predictive tool for identifying potential toxicity targets and pathways, which can guide subsequent experimental validation and provide mechanistic insights that traditional toxicology approaches might miss.